MXene-Based Flexible Supercapacitors: Influence of an Organic Ionic Conductor Electrolyte on the Performance - Vaghasiya, Jayraj V; Mayorga-Martinez, Carmen C; Sofer, Zdenek; Pumera, Martin (ACS applied materials & interfaces, 2020)
Owing to the rise of miniaturized wearable electronic devices in the last decade, significant demands have arisen to obtain high-performance flexible supercapacitors (FSCs). Recently, a lot of research has been focused on developing smart components of FSCs and integrating them into new device configurations. In this work, FSCs based on a Ti3C2 nanosheet (NS) and an organic ionic conductor (OIC)-induced hydrogel as the electrode and the electrolyte, respectively, were used. The FSCs fabricated have three different configurations (sandwich, twisted fiber, and interdigitated) and a comparative study of their electrochemical performance was investigated in terms of cycle stability, bending stability, power density, and energy density. Finally, the experimental validation of practical application was conducted, which suggested excellent electrochemical stability of Ti3C2 NS FSCs for driven commercial electronic gadgets. This study presents mechanically robust, lightweight, high-performance FSCs, which can be assembled in different configurations for powering wearable electronic devices.
Keywords: polymeric gel electrolyte; aqueous hydrogel; 2D materials; two-dimensional materials; organic conductors; wearable electronics; flexible energy storage device